ECONOMIC ANALYSIS OF CITRUS ROSARIO DO SUL/RS: A FOCUS ON THE ADOPTION OF ENVIRONMENTAL CERTIFICATION PROGRAMS - Barbieri, Marciele; Dutra, Cláudia Braga; Bianchini, Nádia Helena; Muniz, Marlove Fátima Brião; Dörr, Andréa Cristina (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611708803 The fruit sector is one of the most important segments of agribusiness in Brazil. In addition to its high profitability and expressive use of hand labor, the fruit stands out as an important alternative to the increase in Brazilian exports of agricultural products. The new market demands reflect the adoption of certification seals that prove the quality and healthiness of the product, the consumer is assured of a safe food whose production respects the environment and the worker. In Rio Grande do Sul, the culture began to be implemented from the year 2000 when several municipalities in the region received funds from the federal government, especially the Rosary South, through the Program for Fruit of the southern half being a beneficiary of the company Citrusul. This article aims to analyze the characteristics of production and marketing of the company, in addition to identifying the possible benefits of a future adoption of environmental certification programs in the citrus industry in the municipality. This article builds on the literature review and as a way to obtain the information necessary to construct this study, we sought through interviews and case study. The study showed that adoption of certification seals would bring the opportunity to access markets more noble and demanding, since the company is already working to have fruit of excellent quality. However, due to the volume of its current production, it is believed that the high costs for registration need not bring a financial return for such an investment.